2019
DOI: 10.1080/02763893.2018.1534177
|View full text |Cite
|
Sign up to set email alerts
|

A GIS Analysis of East Asian Care Gaps in Residential and Assisted Living Facilities in Vancouver, Canada

Abstract: Residential care and assisted living services provide support to seniors who may not have the ability to live independently. However, East Asian residents often do not have sufficient access to culturally-specific activities, which may result in psychosocial stress and isolation. This study presents a geographic analysis method to evaluate spatial distribution of culturally-tailored senior care facilities in Metro Vancouver. We identify geographical disparities, indicating that many East Asian seniors have poo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 13 publications
0
5
0
1
Order By: Relevance
“… Neighborhoods with more utilitarian destinations were associated with excessive sedentary time among older women. Blake Byron Walker 2019 [ 35 ] Canada 286,211 persons comprising the total population aged 65+ years Quantitative: Spatial-epidemiological approach, questionnaire, moving-average linear model Mapping Each facility location in the study area was mapped using GIS. The calculation of local rates used GIS.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Neighborhoods with more utilitarian destinations were associated with excessive sedentary time among older women. Blake Byron Walker 2019 [ 35 ] Canada 286,211 persons comprising the total population aged 65+ years Quantitative: Spatial-epidemiological approach, questionnaire, moving-average linear model Mapping Each facility location in the study area was mapped using GIS. The calculation of local rates used GIS.…”
Section: Resultsmentioning
confidence: 99%
“…Among the 61 articles reviewed, the needs of older adults were categorized into medical care, basic living, transportation, and spiritual needs. A total of 37 articles focused on medical care [ 3 , 15 , 16 , 20 , 21 , 23 , 24 , 28 , 29 , 31 , 32 , 36 , 37 , 39 – 41 , 43 , 45 50 , 50 , 51 , 53 , 54 , 56 , 57 , 60 , 63 68 , 72 ], 14 articles addressed basic living needs [ 14 , 18 , 26 , 27 , 30 , 35 , 38 , 44 , 52 , 55 , 58 , 61 , 62 , 69 ], 8 articles discussed transportation needs [ 19 , 22 , 25 , 34 , 42 , 70 , 71 , 73 ], and 2 articles explored spiritual needs [ 17 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…The Canadian Geographer / Le Géographe canadien 2022, 66(1): [184][185][186][187][188][189][190][191][192][193][194][195][196][197] Residential care in California 195 the distribution of care, with race predicting access to care more than economic resources in certain cases, such as older Hispanics who are the most displaced from residential care in California, as well as Asian older adults with respect to culturally sensitive facilities in Vancouver, Canada (Frochen et al 2019;Walker et al 2019). In terms of policy, only Los Angeles out of the three Cities investigated in this study possesses a planning ordinance aggressively geared toward eldercare facilities, including residential care facilities, that incentivizes such development through a unified permitting process and allowance of facility development in any zone in the city, given the approval of an eldercare facility permit (City of Los Angeles 2006).…”
Section: Discussionmentioning
confidence: 99%
“…Glasby et al., 2019 ; Netten et al., 2005 ). Concerns regarding changing levels of social care supply in relation to demographic trends are also mirrored in wider international contexts (see for example Fret et al., 2019 ; Matei et al., 2018 ; Walker et al., 2019 ).…”
Section: Geographical Approaches To Examine Inequalities In Access To...mentioning
confidence: 99%
“…An example of this approach was included in the Competition and Markets Authority Overall, 90% of all postcode sectors had this level of provision with 19% having two or fewer predominantly located in rural areas. Walker et al (2019) demonstrated how spatial analytical methods can be used to investigate inequalities in access to senior care facilities tailored for specific cultural groups in Vancouver. Their supply/demand analysis enabled the identification of disparities in the availability of such services but as acknowledged by the researchers, used relatively simplistic service ratios of beds per total population for specified cultural groups for census tracts whose geometric centroid was within 2 km walking distance of residential care facilities.…”
Section: What This Paper Addsmentioning
confidence: 99%